EKONOMI POLITIK STRATEGI OPTIMALISASI RANTAI NILAI PETRONAS - , Muhaimin Zulhair Achsin, Dr. Maharani Hapsari, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
International industrial study particularly oil and gas developed simultaneously as the hybrid study. The significance of the contemporary phenomenon of oil-gas company progress requires the complexity of study. The object of this study is Petronas, a Malaysian national oil-gas company with international track records. Intense industry competition requires solid and strong fundamental as well as the cutting-edge strategies to deal with problems. Even though the Petronas comparative advantages in domestic hydrocarbon reserves are lower than petro-states, this company is getting bigger and bigger. In 2005 Petronas was not listed yet as the top 100 world biggest company by revenue but three years later Petronas listed on the rank of 95 and in 2011 at 86, in the several next years it will continuously corrected. The success progress would be studied by using economical and political dimension particularly value chain analysis in the locus of the strategies to optimize value chains. This study examines the historical development in order to build the strong upstream, midstream and downstream fundamental of the company as the optimization strategies both domestically and internationally. The conclusions of this research are the first time pattern strategies build an attractive upstream environment using serial political intervention. The domestic and international strength as the supporting system fully supported by policy rent. Moreover, the improving of internal condition of the company is leadership matter, through Azizan dismantled the blockade that made company less optimal. The mixed of macro domestic under Mahathir and internal under Azizan gave the power to the company to run optimally. In domestic space industrial integration (both vertical and horizontal) and international by expansion since 1990s lead the way. Both of domestic and international could leverage their technology capability and pave the networking. Gas is the main segmentation of this company.